Just the ticket - Garcia, Andy.; MacDowell, Andie; Wenk, Richard; United Artists Pictures; CineSon (Firm) (Santa Monica, CA : Metro Goldwyn Mayer Home Entertainment, 1999)
Longtime New York con man Gary Starke can get his hands on just about anything: floor level seats at a Knicks game, entrance to an exclusive art gallery or first-row concert tickets. But the one thing Gary can't seem to get is the girl of his dreams. Linda , a stunning chef-in-the-making with a soft spot for him, has been accepted into a Parisian cooking school, and decides to leave the city-- and Gary!
Andy Garcia, Andie MacDowell.
DVD, Dolby surround stereo.
Keywords: Comedy films; Films for the hearing impaired; Feature films